Stages of formation of electoral processes in the Republic of Uzbekistan - Boltabayev, Baxtiyor (The Lingua Spectrum, 2025)
During the years of independence, consistent reforms were carried out in the country aimed at establishing an electoral system based on democratic principles, ensuring the political rights and freedoms of citizens, and expanding public participation in state governance. This article provides a detailed analysis of the formation of electoral processes in the Republic of Uzbekistan after gaining independence, including the adoption of laws, decrees, and resolutions related to elections, as well as the development of political parties. Furthermore, the role of the principles of openness, transparency, and fairness in electoral processes and their importance in the development of civil society are examined.